Acute glufosinate-based herbicide treatment in rats leads to increased ocular interleukin-1β and c-Fos protein levels, as well as intraocular pressure. (2019) - Çomaklı, Selim; Sevim, Çiğdem; Kontadakis, George; Doğan, Elif; Taghizadehghalehjoughi, Ali; Özkaraca, Mustafa; Aschner, Michael; Nikolouzakis, Taxiarchis Konstantinos; Tsatsakis, Aristides
Graphical abstract: Highlights: Acute glufosinate-based herbicide (120 μM) treatment induced optic nerve damage. There is a link between exposure to glufosinate and alterations in interleukin-1β and c-Fos immunopositivity. Increased intraocular pressure as measured by tonometry increased in response to glufosinate-based herbicide treatment. Abstract: Glufosinate is a common herbicide with neurotoxic effects, leading to seizures, convulsions and memory loss. Glufosinate indirectly induces glutamate toxicity by inhibiting glutamine synthesis in astrocytes. Here, we studied the acute toxic effects of a glufosinate-based herbicide in rat optic nerve at three doses (40, 80 or 120 μM, equal to 714 or 21 mg/kg bw/day). Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), urea, glucose, calcium, as well as creatinine concentrations were analyzed after 24, 48 and 72 h treatment. Intraocular pressure (IOP) (expressed as the average of both eyes) was measured with a rebound tonometer. Interleukin-1β (IL-1β) and c-Fos expression were determined by immunohistochemistry. The results established that the glufosinate-based herbicide significantly increased IL-1β and c-Fos immunopositivity in the optic nerve (p < 0.05), concomitant with increased IOP. These results suggest that commercial formulations of glufosinate acutely affect the optic nerve.